1977
DOI: 10.1037/h0086530
|View full text |Cite
|
Sign up to set email alerts
|

Insight and figurative language in psychotherapy.

Abstract: Traditionally it has been left to poets and novelists to unravel and discuss the relation between metaphoric language and the experience of insight. The psychological and psychoanalytic commentary on this relationship is fragmentary and implicit. This paper offers both clinical and empirical data which leads to the speculation that novel metaphoric language constitutes not only the contents of specific therapeutic insights but also the thematic interface upon which psychotherapy procedes . A clinical demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 8 publications
0
28
0
2
Order By: Relevance
“…Further support for the co-occurrence of metaphors and insight was reported by Hill and Regan (1991). In their study, however, this relation pertained to the therapist's judgments of his own intentions, rather than to judgments about the client's behavior as was the focus in Barlow et al (1977). That is, Hill and Regan found that the therapist's use of metaphors co-occurred more often than chance with his self-rated intention to encourage insight (i.e., an understanding of the underlying reasons, dynamics, assumptions, or unconscious motivations for cognitions, behaviors, attitudes, or feelings) on the part of the client.…”
Section: Relation Of the Use Of Figurative Language And Psychotherapymentioning
confidence: 97%
See 1 more Smart Citation
“…Further support for the co-occurrence of metaphors and insight was reported by Hill and Regan (1991). In their study, however, this relation pertained to the therapist's judgments of his own intentions, rather than to judgments about the client's behavior as was the focus in Barlow et al (1977). That is, Hill and Regan found that the therapist's use of metaphors co-occurred more often than chance with his self-rated intention to encourage insight (i.e., an understanding of the underlying reasons, dynamics, assumptions, or unconscious motivations for cognitions, behaviors, attitudes, or feelings) on the part of the client.…”
Section: Relation Of the Use Of Figurative Language And Psychotherapymentioning
confidence: 97%
“…In an early investigation of the use of figurative language and the occurrence of insight, Barlow et al (1977) analyzed the same highly successful hour that was analyzed by Pollio and Barlow (1975). They identified two patterns in the transcript of this hour.…”
Section: Relation Of the Use Of Figurative Language And Psychotherapymentioning
confidence: 99%
“…In early studies (e.g., Barlow, H. R. Pollio, & Fine, 1977;McMullen, 1985; H. R. Pollio & Barlow, 1975), researchers relied on the distinction between novel figures (those considered by the receiver to be original contributions within the context of the speaker's communication) and frozen figures (cliched expressions or those words and phrases that are commonly used, accepted parts of speech, such as the legs of a chair), with novel figures judged to be of most signrficance for the tasks of therapy. This distinction is now considered by some researchers (e.g., Amira, 1982; McMullen, 1989) to be an inadequate way of selecting instances for analysis because not all novel figures are implicated in the tasks of therapy and many frozen or conventional figures are indicators of major themes in therapy.…”
Section: Dominance and Nurturance In The Figurative Expressions Of Psmentioning
confidence: 99%
“…It has long been observed that the constant "struggle to find words" to convey "difficult-to-describe sensations, emotions, psychological states, and views of self " (McMullen, 1996, p. 252) is often alleviated, by both therapists and patients, with the help of metaphors. While there has long been an interest in the role of figurative language in psychotherapy (e.g., Arlow, 1979;Barlow, Pollio, & Fine, 1977;Lenrow, 1966;Rogers, 1978), the advent of cognitivist approaches to metaphor and their seeming promise in helping therapists 'access' and 'modify' conceptual systems has sparked a new wave of interest (e.g., Kopp & Craw, 1998;Stott, Mansell, Salkovskis, Lavender, & Cartwright-Hatton, 2010;Wickman, Daniels, White, & Fesmire, 1999), and opened new doors for the practical application of metaphor theory (Tay, 2012). Of particular concern is how metaphors produced by therapists and patients symbolize, introduce, elaborate, and/or change conceptualizations of therapeutically relevant topics such as emotions, careers, relationships, and the like.…”
Section: Cognition Communication and Language In Psychotherapymentioning
confidence: 99%